Pengaruh Besar Sudut pada Servis Bulu Tangkis dengan Gerak Parabola - Audrianita, Nazura; Septiana Rasti, Theresia Adinia; Setiaji, Bayu (Indonesian Journal Publisher, 2023)
Badminton athletes apply various techniques and strategies when competing. One technique is to apply the correct serve to bounce the shuttlecock. The aim of this research is to determine the effect of how big the angle of the racket can be over the net and on target. This research applies an experimental method, which was chosen with the main aim of this research being to test an object. In this context, the focus is on angle variations to determine the optimal angle for the badminton player when serving so that the shuttlecock can fall over the net with different elasticity. In this experiment, the parabolic motion recordings were analyzed using the Tracker application to obtain the initial speed for each angular variation. The shuttlecock's initial speed can be used to calculate the shuttlecock's highest point, the time it reaches its maximum height, and the shuttlecock's furthest distance. The results showed that differences in the initial angle of the backhand serve caused differences in the maximum height, distance and time achieved.